Effect of Cyclic Expansion-Extrusion Process on Microstructure, Deformation and Dynamic Recrystallization Mechanisms, and Texture Evolution of AZ80 Magnesium Alloy - Yong Xue; Shuaishuai Chen; Haijun Liu; Zhimin Zhang; Luying Ren; Bing Bai (Advances in Materials Science and Engineering)
The microstructure, deformation mechanisms, dynamic recrystallization (DRX) behavior, and texture evolution of AZ80 magnesium alloy were investigated by three-pass cyclic expansion-extrusion (CEE) tests. Optical microscopy (OM), electron back-scattered diffraction (EBSD), and X-ray diffraction (XRD) were employed to study microstructure, grain orientation, DRX mechanism, and texture evolution. The results show that the grain sizes decrease continuously with the increase of CEE pass. The grain refinement effect of the first pass is the most remarkable, and there appear a large number of twins. After three-pass CEE, a well-distributed structure with fine equiaxed grains is obtained. With the increase of CEE pass, the deformation mechanism changes from twinning to slipping and the DRX mechanism changes mainly from twinning-induced dynamic recrystallization (TDRX) to rotation dynamic recrystallization (RDRX) and then to continuous dynamic recrystallization (CDRX). The grain misorientation between the new grains and matrix grains deceases gradually, and a relatively small angle misorientation is obtained after three-pass CEE. Grain misorientations of the first two passes are attributed to TDRX and RDRX behaviors, respectively. The grain refinement changes the deformation and DRX mechanisms of CEE process, which leads the (0002) basal texture intensity first decrease and then increase suddenly. Eventually, the extremely strong basal texture is formed after three-pass CEE.